2008
DOI: 10.1007/s10661-008-0473-5
|View full text |Cite
|
Sign up to set email alerts
|

Total concentrations and speciation of heavy metals in soils of the Shenyang Zhangshi Irrigation Area, China

Abstract: The Shenyang Zhangshi Irrigation Area (SZIA) was used for the spreading of municipal and industrial waste water, which is an economic way of irrigating crops, recycling nutrients and water treatment. Long-term irrigation resulted in a severe metal contamination of soils. To identify the soil phases implicated in retaining the metals, sequential extractions were performed. The most predominant metal was cadmium which was mainly associated with mobile, easily soluble and easily reducible fractions. Copper was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…The exchangeable fraction (F 1 ) of zinc is only 6%. This agrees with those reported by other workers (Bulletin 1 Aberdeen 1985; Huang et al 2007;Ratuzny et al 2009). Zn bound to the exchangeable fraction (F 1 ) is found to be negligible, with exception for sites 4, 12, 20, and 28 that have higher values.…”
Section: Zincsupporting
confidence: 93%
“…The exchangeable fraction (F 1 ) of zinc is only 6%. This agrees with those reported by other workers (Bulletin 1 Aberdeen 1985; Huang et al 2007;Ratuzny et al 2009). Zn bound to the exchangeable fraction (F 1 ) is found to be negligible, with exception for sites 4, 12, 20, and 28 that have higher values.…”
Section: Zincsupporting
confidence: 93%
“…This is in agreement with Zn associated [31][32]. The present study also shows a comparison of organic bound higher in sequence to exchangeable fraction with studies [27,33], as shown in Fig. 2(b).…”
Section: Zinc Speciessupporting
confidence: 90%
“…It was also noted that the majority of Cu was existent in the form of oxidizable and residual fractions, accounting for about 80-95.3% of the bulk Cu in all sludge samples. Specifically, the highest oxidizable Cu was obtained in S4 sample and accounted 70.7% of total Cu, being quite similar to the available reports (Ratuzny et al 2009). Traditionally, Cu-organic matter complexes showed the least mobile/stable characteristics, since the combination of the Cu with organic matter was highly dependent on the surrounding condition, e.g., pH, redox-potential, temperature, particularly the quantity of Fe oxides in soils (Silveira et al 2006;Tack and Verloo 1995).…”
Section: Speciation Of Heavy Metals In Different Sludge Samplessupporting
confidence: 89%